Handbook of bilingualism - Kroll, Judith F (Oxford, 2005)
Includes bibliographical references and indexes; How is language acquired when infants are exposed to multiple language input from birth and when adults are required to learn a second language after early childhood? This handbook will be essential reading for cognitive psychologists, linguists, applied linguists, and educators who wish to better understand the cognitive basis of bilingualism and the logic of experimental and formal approaches to language science